Parliamentary Control of Security Information Agency - Statе and Problems - Radivojević, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Even though security services have the same function as before, today they have different tasks and significantly more work than before. Modern security problems of the late 20th and early 21st century require states to reorganize their security services, adapting them to the new changes. The reorganization involves, among other things, giving wider powers of the security services, in order to effectively counter the growing and sophisticated security threats, which may also lead to violations of human rights and freedoms. It is therefore necessary to define the right competence, organization, authority and control of these services. In democratic countries, there are several institutions with different levels of control of security services. Parliament is certainly one of the most important institutions in that control, both in the world and in our country. Powers, finance, the use of special measures and the nature and scope of work of the Security Information Agency are certainly object of the control of the National Assembly. What seems to be the problem is achieving a balance between the need for control of security services and security services to have effective methods for combating modern security problems. This paper presents the legal framework related to the National Assembly control of the Security Intelligence Agency, as well as the practical problems associated with this type of control. We analyzed the role of security culture as one of the factors of that control. In this regard, it provides guidance for the practical work of the members of parliament who control the Security Intelligence Agency, noting in particular the importance of and the need for continuous improvement of security culture representatives.